(untitled) (Scottish Historical and Archaeological Internet Reports, 2011)
Discusses how the Shorewatch Project has involved groups across the country to work on aeolian sites. It gives details of one recent project, demonstrating how archaeologists and local group members can collaborate successfully to save information before it is lost forever.